Neurogenesis From Neural Crest Cells: Molecular Mechanisms in the Formation of Cranial Nerves and Ganglia - Méndez-Maldonado, Karla; Vega-López, Guillermo A.; Aybar, Manuel J.; Velasco, Iván (Frontiers in Cell and Developmental Biology, 2020)
The neural crest (NC) is a transient multipotent cell population that originates in the dorsal neural tube. Cells of the NC are highly migratory, as they travel considerable distances through the body to reach their final sites. Derivatives of the NC are neurons and glia of the peripheral nervous system and the enteric nervous system, as well as non-neural cells. Different signaling pathways triggered by Bone Morphogenetic Proteins, Fibroblast Growth Factors, Wnt proteins, Notch ligands, retinoic acid and Tyrosine Kinase Receptors participate in the processes of induction, specification, cell migration and neural differentiation of the NC. A specific set of signaling pathways and transcription factors are initially expressed in the neural plate border and then in the NC cell precursors to the formation of cranial nerves. The molecular mechanisms of control during embryonic development have been gradually elucidated, pointing to an important role of transcriptional regulators when neural differentiation occurs. However, some of these proteins have an important participation in malformations of the cranial portion and their mutation results in aberrant neurogenesis. This review aims to give an overview of the role of cell signaling and of the function of transcription factors involved in the specification of ganglia precursors and neurogenesis to form the NC-derived cranial nerves during organogenesis.